How renewables are transforming electricity grids: an analysis of Australia's integrated system plan. Issue 3 (8th December 2022) - Longden, Thomas
Abstract: Most countries will require mega programmes of investment to support the transition to higher shares of renewable energy. Large increases in roof-top solar and other grid-scale renewables are changing the way that electricity grids operate and are designed. This paper focuses on the case of Australia, where the Australian Energy Market Operator develops a bi-annual Integrated System Plan (ISP) to provide advice on the development of the electricity grid. The ISP is based on modelling of the future energy system and, accordingly, accounts for a rise in distributed energy generation and other technologies, such as batteries and electric drive vehicles. There are many lessons that can be learned from regions with high shares of renewables, including the importance of grid interconnectivity and storage. This example of rapid change has occurred in a country that did not have a robust national decarbonisation policy, but does have excellent wind and solar resources.